Consumer’s Price Index and measurements errors: some stochastic simulation result - Xanthos, Giorgos; Tserkezos, Dikaios (SPOUDAI Journal of Economics and Business, 2009)
This paper entitled “Consumer’s Price Index and measurements errors: some stochastic simulation results” examines the impact of errors in price recording on the estimation of theConsumer’s Price Index (CPI). By combining techniques of stochastic simulation and the methodology of constructing the Consumer’s Price Index the authors conclude that errors in price recording do in fact have a significant impact on the efficiency of CPI estimation leading many times to excessive variances thus increasing the scope for obtaining unreliable estimations of the inflationary pressures imposed on consumers. JEL Classification: G45